Calcareous Marine Algae, Sodium Bicarbonate and Magnesium Oxide Mixture for Curing Lactic Acidosis in Goats - Hassan, Wafaa; Selim, Hatem Mohamed; Abdelaal, Ahmed Mohamed; Abdallah, Abdelmonem (Journal of Advanced Veterinary Research, 2022)
This study was designed to evaluate the therapeutic efficacy of calcareous marine algae (AcidBuf), sodium bicarbonate and magnesium oxide mixture for the treatment of lactic acidosis in goats. In this study, a total of 57 goats were diagnosed with lactic acidosis and subjected to a therapeutic trial of 4g AcidBuf plus 10 g Na-bicarbonate plus 4g magnesium oxide/head once daily for three days. Before and 72 h after treatment, a clinical examination and blood and ruminal fluid samples were taken. Within 72 h of the therapeutic trial, the clinical signs of lactic acidosis gradually improved and resolved and the rumen pH increased significantly from 5.16Â±0.460 to 6.54Â±0.246. Rumen contraction, rumen fluid physical properties (color, odor and consistency), protozoal motility and ruminal microflora differed significantly toward the normal of healthy goats. Regarding haemgasometry and hematobiochemical parameters, a highly significant decrease in Hb, HCT% , TLC, ALT, AST, creatinine and lactate values and a highly significant increase in blood pH, HCO3-, pCO2, serum urea, total antioxidant capacity (TAC) and Î²-hydroxybutyric acid (Î²HBA) were recorded compared to the pre-treatment values. The current study concluded that calcareous marine algae, sodium bicarbonate and magnesium oxide mixture is very helpful in minimizing the severity of ruminal lactic acidosis in goats and could be used as the therapy of choice.